Three-keys digital media in strengthening brand awareness at The Vibes Night Club, France - Putu Rian Arde Surya; Alain Fournier; I Ketut Sutama; Muhamad Nova (Politeknik Negeri Bali, 2023)
In order to reach and influence potential online customers, there was often an overlap among paid media, owned media, and earned media at The Vibes Nightclub, France. Solving this problem required the integration of campaigns, resources, and infrastructure, which could develop online products, services, and brand awareness. The methodology used in this study is qualitative, using the descriptive approach with display and verification technique analyses at The Vibes Nightclub. The results showed that paid media is done through activities such as Search Engine Marketing (SEM). Further, owned media focus on Facebook, Instagram, and Google pages owned by the club, like Search Engine Optimization (SEO). Earned media includes word of mouth on social media, live, and conversations. Their activities had a significant effect on strengthening brand awareness. In this regard, consistency and optimism in digital marketing activities need to be maintained because these things can improve and maintain existence and sustainability. Furthermore, using more digital platforms and analytics digital should be improved for the targeted results and sustainability of the business.